Designing women: modernist mass culture and the formation of the female body. Issue 1 (2nd January 2019) - Watts, Kara
ABSTRACT: This essay argues for charm as feminist heuristic through which we may re-examine contemporary theories of gendered embodiment. Charm as a form of bodily habitation for women in modernity seems to be another facet of cultural or sociopolitical control over female subjects. However, this is not the entire picture. I argue that charm denotes a superficiality or refusal of depth in female embodiment that interrupts, yet also acknowledges, the physiological marks inscribed upon socially written bodies by addressing theories of the body. I then locate these interruptions in the early experimental poetry of Gertrude Stein and in selected works of mass culture including magazines, beauty pamphlets, and self-help books. Ultimately, by looking to Stein and these cultural texts, I find that women's charm exhibited by their bodies is not what it seems. There is both a seem and a seam to women's bodies, a fissure or stitching that appears when we examine how bodies are formed. This occurs through a repetition that – in contrast to contemporary theories of gendered embodiment by Judith Butler, bodily biopower by Michel Foucault, or bodily mattering in feminist new materialism – presents the body as a styled set of desires.